Osmophores and petal surface traits in Bignonieae species - Macedo, Karise Mamede [UNESP]; Tunes, Priscila [UNESP]; de Almeida Gonçalves, Letícia; Canaveze, Yve; Guimarães, Elza [UNESP]; Machado, Silvia Rodrigues [UNESP] (Springer Nature, 2023)
This study characterizes the osmophores and corolla traits in 18 species of Bignonieae Dumort., a Bignoniaceae tribe occurring in the Cerrado, a neotropical savanna in Brazil. To detect osmophore distribution, whole, newly opened flowers were immersed in Neutral Red Solution. Samples from the corolla tube and lobes were also fixed and analyzed micromorphologically, anatomically, and histochemically. The osmophores showed six markedly different distribution patterns that were not clearly associated with histological features. In most species, osmophores comprised papillose secretory epidermises and a few layers of subepidermal parenchyma. Starch grains, lipid droplets, and terpenes were detected in osmophores. An ornamented cuticle, cuticular folds, glandular and non-glandular trichomes, raised stomata and epicuticular wax granules are common traits in the species studied and may be useful in determining the taxonomy of the group. We found that 94% of the species visited by bees had papillose epidermises while the single hummingbird-pollinated species presented a flattened epidermis. Variations in osmophore pattern among species visited by bees, including variations within the same plant genus, are novel finding. Additionally, the Bignonieae species visited by bees presented a textured corolla surface, which has been reported as facilitating bee attachment and movement towards the floral resource. Future studies with a greater number of Bignonieae species and more detailed pollinator behavioral assays may help in the interpretation of the variations in corolla traits and functional relationships between flowers and pollinators.
Keywords: Anatomy; Bee-pollination; Cuticular folds; Histochemistry; Hummingbird pollination; Micromorphology; Osmophores